Workers’ Power and Intentional Learning among Non-managerial Workers: A 2004 Benchmark Survey - Livingstone, David; Raykov, Milosh (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2008)
This paper explores relations of workers’ power, in terms of unionization and delegated workplace authority, with incidence of participation in adult education and job-related informal learning activities. Empirical analysis is based primarily on the first Canadian survey to document both aspects of workers’ power and both formal and informal learning. Prior inconsistent research on unionization and adult education is critically reviewed. The current study focuses on non-managerial employees between 25 and 64. The findings of this 2004 survey, as well as secondary analysis of other relevant surveys, confirm that union membership is consistently positively related to both participation in adult education and some informal learning topics. Delegated workplace authority also has positive effects on both adult education and some informal learning topics. While delegated workplace authority is not related to unionization, their positive effects on workers’ intentional learning are additive. Implications of these findings for further research and optimizing workplace learning are discussed.